Happy feet : the Savoy Ballroom Lindy Hoppers and me - Michelson, Richard (Gulliver Books/Harcourt, 2005)
A young boy who loves to dance listens as his father retells the story of the night he was born, which coincided with the opening of the Savoy Ballroom in Harlem.